MENINGKATKAN MOTORIK KASAR ANAK USIA 4-5 TAHUN MELALUI SENI TARI KREASI DI TAMAN KANAK- KANAK - Sephira Nurma Elinda; Dodi Harianto; Achmad Fadlan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The gross motor skills of 4–5-year-old children at Mendalo Darat State Kindergarten No. 15 have not yet developed optimally, as evidenced by their poor balance, agility, and flexibility during physical activities. This situation is influenced by teaching methods that remain conventional, resulting in children being less active and easily bored. This study aims to improve the gross motor skills of 4–5-year-old children through the application of the Serampang Laut creative dance. The study used a Classroom Action Research (CAR) approach based on the Kemmis and McTaggart model, conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The research subjects consisted of 12 children in Group A at State Kindergarten 15 Mendalo Darat. Data collection techniques included observation, interviews, and documentation, while data analysis was conducted using both quantitative and qualitative descriptive methods based on indicators of balance, agility, and flexibility. The results of the study indicate that the implementation of the Serampang Laut creative dance was able to gradually improve the children’s gross motor skills in each cycle. The children became more active and enthusiastic and were able to perform basic movements with better body coordination. The percentage of students meeting the classical mastery criteria at the end of the study reached 96%, exceeding the established success indicator of 85%. Thus, the Serampang Laut creative dance art form has proven effective as a fun and meaningful learning alternative for stimulating the gross motor development of young children